2008
DOI: 10.1111/j.1755-148x.2008.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanophores in the stripes of adult zebrafish do not have the nature to gather, but disperse when they have the space to move

Abstract: SummaryAnimal skin pattern is one of the good model systems used to study the mechanism of pattern formation.Molecular genetic studies with zebrafish have shown that pigment cells play a major role in the mechanism of stripe formation. Among the variety of cellular events that may be involved in the mechanism, aggregation of melanophores has been suggested as an important factor for pattern formation. However, only a few experimental studies detected the migration ability of melanophores in vivo. Here, we trie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(113 citation statements)
references
References 30 publications
(42 reference statements)
12
99
2
Order By: Relevance
“…In this system, we found that the interaction was not a simple repulsive response but a more active and continuous run-and-chase movement. The run-and-chase movement was quite similar to the exclusive movement of melanophores in vivo (16). The similarity between these movements suggested that the cell movement observed in vitro was related to pattern formation in vivo.…”
Section: Cell Movement Induced By Contact Between Xanthophores Andmentioning
confidence: 51%
See 2 more Smart Citations
“…In this system, we found that the interaction was not a simple repulsive response but a more active and continuous run-and-chase movement. The run-and-chase movement was quite similar to the exclusive movement of melanophores in vivo (16). The similarity between these movements suggested that the cell movement observed in vitro was related to pattern formation in vivo.…”
Section: Cell Movement Induced By Contact Between Xanthophores Andmentioning
confidence: 51%
“…Although pigment cell interaction has been suggested to play an important role in pigment patterning (16,19), the details of the interaction remained to be elucidated, because an appropriate system for observation did not exist. In this report, we established a unique protocol to harvest pigment cells and observe them in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental studies have been conducted to elucidate the cellular interactions that drive pattern formation. These experiments range from using laser or transgenic ablation to remove pigment cells in vivo [5,7,12,16,17] to observing pairs of cells interacting in vitro [18,19] and exploring altered cell behaviour through mutational analysis, transplantation and other methods [14,20,21]. Researchers also study time-lapse images of wild-type development [10,15,16,20,22] and analyse mutations [4,8,10,11,[14][15][16][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Because we and others observed the migration of pigment cells and their precursors, we wonder if this conflict might be from a difference in some experimental conditions (8)(9)(10)(11). More fundamentally, however, migration is not a crucial requirement of our Turing-based model.…”
mentioning
confidence: 99%